HUBUNGAN AKTIFITAS PROLANIS DENGAN KEPATUHAN DIET PASIEN DIABETES MELLITUS - Janah, Esti Nur; Rindu, Rindu; Dwi Ayu, Yennyka; Alamsyah, Putri Rahmah; Kaluku, Khartini (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
One indicator of success in maintaining stable blood sugar levels in diabetics is dietary adherence. Dietary adherence is essential to successfully control blood sugar levels. Patient non-compliance with diet can have a negative impact on the severity of diabetes experienced, thus requiring a longer treatment process. Based on an initial survey of around 210 patients recorded as participating in PROLANIS throughout 2022, only 30 people have routinely participated since the pandemic began in December 2021 at Puskesmas Simpang Tiga. This study aims to determine the relationship between prolanis activities and dietary compliance of patients with diabetes mellitus. This type of research is quantitative with a cross sectional approach. The research was conducted in 2023 at the Simpang Tiga Health Center. The research sample amounted to 138 respondents. Data collection tools using a research questionnaire. Data analysis was carried out univariate and bivariate. The results showed that there was a relationship between medical consultation (p value 0.000) and group education (p value 0.000) with dietary compliance in the prolanis program. This study recommends that Puskesmas Simpang Tiga, especially Puskesmas officers, organize the PROLANIS program in improving health monitoring for diabetes mellitus respondents and encourage respondents to attend PROLANIS activities via SMS gateway or Whatsapp group in order to help improve compliance.Keywords: Education, Prolanis, Health Center.